The effects of diverse fidelity scenarios on stress in medical students when taking patients' medical histories: A longitudinal study - Herrmann-Werner, Anne; Erschens, Rebecca; Fries, Maximilian; Wehner, Hannah; Zipfel, Stephan; Festl-Wietek, Teresa (Stress and health, 2023)
Taking patients' medical history correctly is the basis of diagnosis and therapy. Medical students as a vulnerable group may perceive patient-physician interactions as stressful. This study examines stress among medical students in different degrees of fidelity when taking a patient's medical history. In this longitudinal study, students' stress levels were assessed during scenarios with different degrees of fidelity (role-play, simulated patient encounters and real patient encounters) using standardised questionnaires (State-Trait Anxiety Inventory and a distress scale) and the physiological measurement of heart rate variability. The stress level of participating medical students (N = 128) was expected to significantly increase during scenarios of increasing fidelity (Mroleplay = 2.08 ± 0.92; SPEs: Msimulatedpatient = 2.68 ± 1.08; RPEs: Mrealpatient = 3.35 ± 1.08; p < 0.001). Whereas physiological stress was significantly higher with real patients (N = 106), psychological stress was not affected by the fidelity of the scenarios (N = 85). Medical students experienced stress when taking patients' medical history. Medical students might be unaware of their perceived stress based on the results. Thus, they should know how to cope with stress in such situations.
Erstmals veröffentlicht: 26. Oktober 2022
Gesehen am 25.06.2024